The Present Perfect from a Diachronic Perspective: An Analysis of Aspectual and Tense Constructions - Žic Fuchs, Milena; Broz, Vlatko (2012)
According to some historical linguists, the early English HAVE + past participle construction had only one meaning (e.g. Mustanoja 1960: 499-500, Carey 1994), namely the resultative perfect. However, recent research has demonstrated that the Old English HAVE + past participle construction has much more in common with the Modern English present perfect than was previously thought (Lee 2003 and Łęcki 2010). Reading of the literature of both diachronic and synchronic analyses opens up terminological issues of the usage of “uses”, “meanings” and “functions”. Such terminological ambiguity is in fact a reflection of the uncertainty as to the true nature of HABBAN + past participle construction or the present perfect in Modern English. A recent synchronic corpus-based analysis of the present perfect (Žic Fuchs 2009) has shown that we are faced with four constructions each reflecting a specific meaning, the most frequent two being the resultative and the experiential, which are primarily aspectually marked. The other two meanings, the perfect of persistent situation and the perfect of recent past, exhibit lower frequency counts and features of relative tense. This study differs from views expressed by authors such as Klein (1994) and Declerck (2006) have gone to great lengths to prove the status of the present perfect as belonging to the tense system. On the other hand, Lyons (1968: 315-316) and Comrie (1976) see it predominantly as aspect. On the basis of an extensive analysis of HAVE + past participle constructions in Old and Middle English corpora (The York-Toronto-Helsinki Parsed Corpus of Old English Prose and Penn-Helsinki Parsed Corpus of Middle English, Second Edition), the development of aspectual and relative tense meaning constructions will be demonstrated. Frequency of occurrence of different meaning constructions will be compared to contemporary evidence found in Modern English corpora. Thus the basic aim of this paper is to provide an overview of the development of meaning constructions that we find in Modern English present perfect. References Carey, K. (1994) “The grammaticalization of the Perfect in Old English: An Account Based on Pragmatics and Metaphor” In: Pagliuca, William (ed.) Perspectives on grammaticalization. Amsterdam Studies in the Theory and History of Linguistic Science. Amsterdam-Philadelphia: John Benjamins Publishing Company, pp. 103-117 Comrie, B. (1976) Aspect, Cambridge: Cambridge University Press Declerck, R. (2006) The Grammar of the English Tense System, The Grammar of the English Verb Phrase, Vol I, Mouton de Gruyter, Berlin, New York Klein, W. (1994) Time in Language. Routledge: London and New York Łęcki, A. (2010) Grammaticalisation Paths of Have in English. Frankfurt am Main: Peter Lang Lee, J.H. (2003) “The “have” perfect in Old English: How close was it to the Modern English perfect?” In Minkova, D. & Stockwell, R. (eds.) Studies in the History of the English Language: A Millennial Perspective. Berlin-New York-Amsterdam: Mouton de Gruyter. pp. 373-97 Lyons, J. (1968). Introduction to Theoretical Linguistics. Cambridge University Press Michaelis, L.A. (1998) Aspectual Grammar and Past-Time Reference. London and New York: Routledge Mustanoja, T.F. (1960) A Middle English Syntax. Helsinki: Société Néophilologique. Žic Fuchs, M. (2009) Kognitivna lingvistika i jezične structure: engleski present perfect, Zagreb: Nakladni zavod Globus
Projekt MZOS
ENG